Overview of Fourth Generation Reactors Studied at the Universidade Federal de Minas Gerais (Brazil) - Clarysson Alberto Mello da Silva; Anderson Altair Pinheiro de Macedo; Maurício Gilberti; Fabiano Cardoso da Silva; Isabella Resende Magalhães; Antonella Lombardi Costa; Claubia Pereira (Brazilian Journal of Radiation Sciences, 2024)
This paper presents the results of the studies about the Fourth Generation Reactors developed at DENU-UFMG, such as the Very High Temperature Reactor (VHTR), Molten Salt Breeder Reactor (MSBR), Sodium Fast Reactor (SFR) and Gas-cooled Fast Reactor (GFR). These studies evaluate neutronic parameters of the nuclear system at steady state and during the burnup using computer models developed at DENU-UFMG using SCALE 6.0 (KENO-VI/ORIGENS), MCNPX 2.6.0 and MCNP5. The results show that the adopted methodologies confirm the capabilities of the codes to simulate specific situations in steady state or transient operating conditions.